DEIKSIS PADA CHANNEL YOUTUBE OFFICIAL HADIAH SPESIAL NADIEM MAKARIEM UNTUK NONO SI JENIUS MATEMATIKA: ANALISIS PRAGMATIK - Santa Rosa Br Pardosi; Sinta M Pasaribu; Frinawaty Lestarina Baru; Emasta Evayanti Simanjuntak; Sintya Klolanta Br Ginting (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This study aims to analyze the various kinds of deixis contained in conversations on the Official Inews Youtube channel with the title "Nadiem Makarim Special Prize for Nono the Mathematical Genius". The conversation contains a discussion about Nono who won an international math competition. This study used descriptive qualitative method. The object of the research is the conversation between Prabu, Nono, Minister of Education Nadiem Makarim, Mama Nur, and Ibu Aguslina. The research techniques used are observation techniques, listening techniques, and note-taking or writing techniques. Based on the analysis results, five deixis were found. First, there are 114 personal deixis in the form of the words I, we, we, you, he, his, and they. Second, there are 13 place deixis in the form of the words there, here, that, and this. Third, there are 12 time deixis in the form of the words yesterday, earlier, then, and later. Fourth, the social deixis of 90 older siblings, mas, sir, mama, madam, madam, madam, prof, uncle, and ministers. Fifth, there are 110 discourse deixis in the form of the word this, that, like this, that way, and like that.